The influence of the grip acceleration on club head rotation during a golf swing - Furukawa, K.; Tsujiuchi, N.; Ito, A.; Matsumoto, K.; Ueda, M.; Okazaki, K. (Proceedings, 2018)
Golfers aim to hit the golf ball correctly and maximize its displacement. It is necessary to predict shaft movement during a golf swing via simulation in order to determine the appropriate shaft for each individual golfer`s swing. Our previous study simulating golf club movement during the golf swing demonstrated 3D club movement via a finite element method simulation model with shaft flexibility. In this study, we added torque, taking into account the combination of grip acceleration and club head centroid, to the simulation model. In order to determine the influence of the torque, we then compared the measured and simulated results of shaft deflection and club head kinematics [HS (club head speed), Path (path angle), AA (attack angle), and FA (face angle)]. There was no significant torque influence for HS, AA, or shaft deflection. However, the Path and FA simulations were close to the measured values.